Preparing for a dermatopathology quiz - Biju Vasudevan; Manas Chatterjee; Nikhil Moorchung; Shekar Neema (Wolters Kluwer Medknow Publications, 2014)
Dermatopathology is one of the key aspects in dermatological diagnosis and is of immense value to the practicing dermatologist as well as residents pursuing dermatology as a career. It is a visual medium of understanding the subject, and is therefore ideal to be tested similarly. Dermatopathology quiz has become a part and parcel of most scientific deliberations, and is therefore an essential requirement of the postgraduate curriculum. Preparing for a dermatopathology quiz is tougher than preparing for a normal clinical quiz because of the lesser importance given for it in the syllabus of postgraduation and also due to the lack of resources either in getting microscopic sessions arranged or due to lack of flair of the subject compared to cosmetology or dermatosurgery. This review was done with the purpose of educating both the students and quizmasters as to how to prepare for a dermatopathology quiz. It is a unique proposal and, therefore, is gathered from more of personal experience, experience gained from watching quizzes conducted by experienced quizmasters, and also from the advice gained from masters of the subject in relation to the quiz.